Sosialisasi Silvofishery Budidaya Kepiting dengan Sistem Kombinasi Bambu Jaring (KOMBUJA) Sebagai Pelaksanaan SDG’S 14 di Desa Mumbul Sari Lombok Timur - Diniarti, Nanda; Dewi Putri Lestari; Laily Fitriani Mulyani; Alis Mukhlis; Ismi Usman Idris (Universitas Mataram, 2025)
Mangrove areas serve as habitats for many marine creatures. The mangrove area in Mumbul Sari Village is under conservation status, with activities designed to protect, restore, and enhance the quality and diversity for sustainable use. Crab farming, using the Bamboo Net (KOMBUJA) system, supports these goals. In Seruni Mumbul Village, socialization activities aimed to 1) introduce and promote silvofishery principles, 2) increase understanding of general crab farming, and 3) introduce the Kombuja crab farming system to the Pelita Seruni POKMASWAS group. The three main methods deployed—preparation, socialization, and participant counseling—were carried out at the Padak sia Mosque with 12 attendees. Initially, participants had little understanding of silvofishery and crab physiology. By the end, more than 75% gained an understanding of basic silvofishery principles, crab characteristics, cultivation methods, and variations of the KOMBUJA system for mangrove crab farming.